Molecular markers of angiogenesis and metastasis in lines of oral carcinoma after treatment with melatonin - Goncalves, Naiane do Nascimento; Rodrigues, Rodrigo Ventura [UNESP]; Jardim-Perassi, Bruna Victorasso [UNESP]; Moschetta, Marina Gobbe; Lopes, Juliana Ramos [UNESP]; Colombo, Jucimara; Zuccari, Debora Aparecida Pires de Campos [UNESP] (Bentham Science Publ Ltd, 2014)
Background: Oral cancer is the most common type of head and neck cancer and its high rate of mortality and morbidity is closely related to the processes of angiogenesis and tumor metastasis. The overexpression of the pro-angiogenic genes, HIF-1 alpha and VEGF, and pro-metastatic gene, ROCK-1, are associated with unfavorable prognosis in oral carcinoma. Melatonin has oncostatic, antiangiogenic and antimetastatic properties in several types of neoplasms, although its relationship with oral cancer has been little explored. This study aims to analyze the expression of the genes HIF-1 alpha, VEGF and ROCK-1 in cell lines of squamous cell carcinoma of the tongue, after treatment with melatonin.Methods: SCC9 and SCC25 cells were cultured and cell viability was assessed by MTT assay, after treatment with 100 mu M of CoCl2 to induce hypoxia and with melatonin at different concentrations. The analysis of quantitative RT-PCR and the immunocytochemical analysis were performed to verify the action of melatonin under conditions of normoxia and hypoxia, on gene and protein expression of HIF-1 alpha, VEGF and ROCK-1.Results: The MTT assay showed a decrease in cell viability in both cell lines, after the treatment with melatonin. The analysis of quantitative RT-PCR indicated an inhibition of the expression of the pro-angiogenic genes HIF-1 alpha (P < 0.001) and VEGF (P < 0.001) under hypoxic conditions, and of the pro-metastatic gene ROCK-1 (P < 0.0001) in the cell line SCC9, after treatment with 1 mM of melatonin. In the immunocytochemical analysis, there was a positive correlation with gene expression data, validating the quantitative RT-PCR results for cell line SCC9. Treatment with melatonin did not demonstrate inhibition of the expression of genes HIF-1 alpha, VEGF and ROCK-1 in line SCC25, which has different molecular characteristics and greater degree of malignancy when compared to the line SCC9.Conclusion: Melatonin affects cell viability in the SCC9 and SCC25 lines and inhibits the expression of the genes HIF-1 alpha, VEGF and ROCK-1 in SCC9 line. Additional studies may confirm the potential therapeutic effect of melatonin in some subtypes of oral carcinoma.
Keywords: Cell lines; HIF-1 alpha; ROCK-1; melatonin; oral cancer; VEGF